Significance of the prognostic nutritional index in patients with esophageal squamous cell carcinoma - Feng JF; Chen QX (Dove Medical Press, 2013)
Ji-Feng Feng, Qi-Xun Chen Department of Thoracic Surgery, Zhejiang Cancer Hospital, Key Laboratory Diagnosis and Treatment Technology on Thoracic Oncology, Hangzhou, People's Republic of China Background: The prognostic nutritional index (PNI) is related to the prognosis in many cancers; however, its role in esophageal cancer is still controversial. Further, controversy exists concerning the optimal cut-off points for PNI to predict survival. The aim of this study was to determine the prognostic value of PNI and propose the optimal cut-off points for PNI in predicting cancer-specific survival (CSS) in esophageal squamous cell carcinoma (ESCC). Methods: This retrospective study included 375 patients who underwent esophagectomy for ESCC. The PNI was calculated as 10 × serum albumin (g/dL) + 0.005 × total lymphocyte count (per mm3). With the help of the fit line on the scatter plot, we classified the patients into three categories according to the PNI, ie, >52, 42–52, and <42. Results: Our study showed that PNI was associated with tumor length (P=0.007), T grade (P=0.001), and N staging (P<0.001). The 5-year CSS in patients with PNI <42, 42–52, and >52 were 11.0%, 39.1%, and 55.2%, respectively (P<0.001). Multivariate analysis showed that PNI was a significant predictor of CSS (42–52 versus >52, P=0.011; <42 versus PNI >52, P<0.001). Conclusion: PNI is a predictive factor for long-term survival in ESCC. The survival rate of ESCC can be discriminated between three groups, ie, PNI ,42, 42–52, and .52. Keywords: esophageal squamous cell carcinoma, prognostic nutritional index, prognostic factor, survival